2015
DOI: 10.1242/jeb.104828
|View full text |Cite
|
Sign up to set email alerts
|

Insight into post-transcriptional gene regulation: stress-responsive microRNAs and their role in the environmental stress survival of tolerant animals

Abstract: Living animals are constantly faced with various environmental stresses that challenge normal life, including: oxygen limitation, very low or high temperature, as well as restriction of water and food. It has been well established that in response to these stresses, tolerant organisms regularly respond with a distinct suite of cellular modifications that involve transcriptional, translational and posttranslational modification. In recent years, a new mechanism of rapid and reversible transcriptome regulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 57 publications
0
47
0
2
Order By: Relevance
“…A number of reviews have reported upregulation of many genes during hibernation process (Andrews, ; Carey, Andrews, & Martin, ; Storey & Storey, ). All the above discussion shows that during hibernation, miRNAs and their target genes could be involved in hypometabolic activities as shown in (Table ) (Biggar & Storey, ). The readers are referred to previously published excellent reviews for detailed discussion of miRNA biogenesis, mechanism of action, and translational repression of miRNAs (Arfat et al, ; Bartel, ; Kim, ; Carrington & Ambros, ; Kim, Han, & Siomi, ; O'Connell, Rao, Chaudhuri, & Baltimore, ; Winter, Jung, Keller, Gregory, & Diederichs, ).…”
Section: Introductionmentioning
confidence: 98%
“…A number of reviews have reported upregulation of many genes during hibernation process (Andrews, ; Carey, Andrews, & Martin, ; Storey & Storey, ). All the above discussion shows that during hibernation, miRNAs and their target genes could be involved in hypometabolic activities as shown in (Table ) (Biggar & Storey, ). The readers are referred to previously published excellent reviews for detailed discussion of miRNA biogenesis, mechanism of action, and translational repression of miRNAs (Arfat et al, ; Bartel, ; Kim, ; Carrington & Ambros, ; Kim, Han, & Siomi, ; O'Connell, Rao, Chaudhuri, & Baltimore, ; Winter, Jung, Keller, Gregory, & Diederichs, ).…”
Section: Introductionmentioning
confidence: 98%
“…The genetic tools available for gene-environment interaction studies in killifish have recently expanded with the publication of a killifish reference genome (Burnett et al, 2007; Reid et al, 2017). The sequenced genome enables investigation of gene regulatory mechanisms at multiple levels (genetic, epigenetic, transcriptional, post-transcriptional) that facilitate the ability of killifish to acclimate to changes in their environment, and in particular the role of non-coding RNAs, which have been identified as mediators of survival responses in organisms tolerant of environmental stress (Biggar and Storey, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs bind to complementary mRNA sequences to tag them for degradation or sequestration into subcellular particles for storage. MicroRNA control over specific mRNAs can regulate entire metabolic processes, including apoptosis 4 . For instance, miR-21 binds to mRNA transcripts of pro-apoptotic proteins APAF-1, caspase-3 and PCNA4, leading to their degradation/sequestration to prevent cell death.…”
mentioning
confidence: 99%
“…For instance, miR-21 binds to mRNA transcripts of pro-apoptotic proteins APAF-1, caspase-3 and PCNA4, leading to their degradation/sequestration to prevent cell death. MiR-21 levels rose in squirrel muscle during hibernation but decreased in brown fat and also in muscle of little brown bats, suggesting that they regulate apoptosis in a tissue- and species-specific manner 4 . New research also shows that low temperature strengthens binding interactions of microRNAs and target mRNAs 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation